Dominance of 'Gallionella capsiferriformans' and heavy metal association with Gallionella‐like stalks in metal‐rich pH 6 mine water discharge. Issue 1 (26th September 2015) - Fabisch, M.; Freyer, G.; Johnson, C. A.; Büchel, G.; Akob, D. M.; Neu, T. R.; Küsel, K.
Abstract: Heavy metal‐contaminated, pH 6 mine water discharge created new streams and iron‐rich terraces at a creek bank in a former uranium‐mining area near Ronneburg, Germany. The transition from microoxic groundwater with ~5 mm Fe(II) to oxic surface water may provide a suitable habitat for microaerobic iron‐oxidizing bacteria (FeOB). In this study, we investigated the potential contribution of these FeOB to iron oxidation and metal retention in this high‐metal environment. We (i) identified and quantified FeOB in water and sediment at the outflow, terraces, and creek, (ii) studied the composition of biogenic iron oxides ( Gallionella ‐like twisted stalks) with scanning and transmission electron microscopy (SEM, TEM) as well as confocal laser scanning microscopy (CLSM), and (iii) examined the metal distribution in sediments. Using quantitative PCR, a very high abundance of FeOB was demonstrated at all sites over a 6‐month study period. Gallionella spp. clearly dominated the communities, accounting for up to 88% of Bacteria, with a minor contribution of other FeOB such as Sideroxydans spp. and ' Ferrovum myxofaciens '. Classical 16S rRNA gene cloning showed that 96% of the Gallionella ‐related sequences had ≥97% identity to the putatively metal‐tolerant ' Gallionella capsiferriformans ES‐2', in addition to known stalk formers such as Gallionella ferruginea and Gallionellaceae strain R‐1. Twisted stalks from glass slides incubated in water and sediment were composed of the Fe(III) oxyhydroxide ferrihydrite, as well as polysaccharides. SEM and scanning TEM‐energy‐dispersive X‐ray spectroscopy revealed that stalk material contained Cu and Sn, demonstrating the association of heavy metals with biogenic iron oxides and the potential for metal retention by these stalks. Sequential extraction of sediments suggested that Cu (52–61% of total sediment Cu) and other heavy metals were primarily bound to the iron oxide fractions. These results show the importance of ' G. capsiferriformans ' and biogenic iron oxides in slightly acidic but highly metal‐contaminated freshwater environments.